Economic policy under uncertainty : the role of truth and accountability in policy advice - Mooslechner, Peter; Schuberth, Helene; Schürz, Martin (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2004)
The book maintains that the question of truth and accountability has not received particular attention in the literature on economic methodology. It goes to argue that pragmatic theories relate concepts of truth to the beliefs, thoughts and intentional actions of individuals, blurring the relationship between theory and practice.
Includes bibliographical references and index.
osc 26/8/16
Loans
Keywords: Economic policy; Uncertainty; Truth; Responsibility; Economics